Light propagation in a photonic crystal fiber infiltrated with mesogenic azobenzene dyes - Budaszewski, Daniel; Woliński, Tomasz R (Photonics Letters of Poland, 2017)
In this paper, light propagation in an isotropic photonic crystal fiber as well in a silica-glass microcapillary infiltrated with a mesogenic azobenzene dye has been investigated. It appeared that light spectrum guided inside the photonic crystal fiber infiltrated with the investigated azobenzene dye depends on the illuminating wavelength of the absorption band and on linear polarization. Also, alignment of the mesogenic azobenzene dye molecules inside silica glass microcapillaries and photonic crystal fibers has been investigated. Results obtained may lead to a new design of optically tunable photonic devices. Full Text: PDF References P. Russell. St. J. "Photonic-Crystal Fibers", J. Lightwave Technol. 24, 4729 (2006). CrossRef T. Larsen, A. Bjarklev, D. Hermann, J. Broeng, "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Exp. 11, 2589 (2003). CrossRef D. C. Zografopoulos, A. Asquini, E. E. Kriezis, A. d'Alessandro, R. Beccherelli, "Guided-wave liquid-crystal photonics", Lab Chip, 12, 3598 (2012). CrossRef F. Du, Y-Q. Lu, S-T. Wu, "Electrically tunable liquid-crystal photonic crystal fiber", Appl. Phys. Lett 85, 2181 (2004) CrossRef D. C. Zografopoulos, E. E. Kriezis, "Tunable Polarization Properties of Hybrid-Guiding Liquid-Crystal Photonic Crystal Fibers", J. Lightwave Technol. 27 (6), 773 (2009) CrossRef S. Ertman, M. Tefelska, M. Chychłowski, A. Rodriquez, D. Pysz, R. Buczyński, E. Nowinowski-Kruszelnicki, R. Dąbrowski, T. R. Woliński. "Index Guiding Photonic Liquid Crystal Fibers for Practical Applications", J. Lightwave Technol. 30, 1208 (2012). CrossRef D. Noordegraaf, L. Scolari, J. Laegsgaard, L. Rindorf, T. T. Alkeskjold, "Electrically and mechanically induced long period gratings in liquid crystal photonic bandgap fibers", Opt. Expr. 15, 7901 (2007) CrossRef M. M. Tefelska, M. S. Chychlowski, T. R. Wolinski, R. Dabrowski, W. Rejmer, E. Nowinowski-Kruszelnicki, P. Mergo, "Photonic Band Gap Fibers with Novel Chiral Nematic and Low-Birefringence Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst. 558(1), 184 (2012). CrossRef S. Mathews, Y. Semenova, G. Farrell, "Electronic tunability of ferroelectric liquid crystal infiltrated photonic crystal fibre", Electronics Letters, 45(12), 617 (2009). CrossRef V. Chigrinov, H-S Kwok, H. Takada, H. Takatsu, "Photo-aligning by azo-dyes: Physics and applications", Liquid Crystals Today, 14:4, 1-15, (2005) CrossRef A. Siarkowska, M. Jóźwik, S. Ertman, T.R. Woliński, V.G. Chigrinov, "Photo-alignment of liquid crystals in micro capillaries with point-by-point irradiation", Opto-Electon. Rev. 22, 178 (2014); CrossRef D. Budaszewski, A. K. Srivastava, A. M. W. Tam, T. R. Woliński, V. G. Chigrinov, H-S. Kwok, "Photo-aligned ferroelectric liquid crystals in microchannels", Opt. Lett. 39, 16 (2014) CrossRef J-H Liou, T-H. Chang, T. Lin, Ch-P. Yu, "Reversible photo-induced long-period fiber gratings in photonic liquid crystal fibers", Opt. Expr. 19, (7), 6756, (2011) CrossRef T. T. Alkeskjold, J. Laegsgaard, A. Bjarklev, D. S. Hermann, J. Broeng, J. Li, S-T. Wu, "All-optical modulation in dye-doped nematic liquid crystal photonic bandgap fibers", Opt. Exp, 12 (24), 5857 (2004) CrossRef K. Ichimura, Y. Suzuki, T. Seki, A. Hosoki, K. Aoki, "Reversible change in alignment mode of nematic liquid crystals regulated photochemically by command surfaces modified with an azobenzene monolayer", Langmuir, 4, 1214 (1988) CrossRef http://www.beamco.com/Azobenzene-liquid-crystals DirectLink K. A. Rutkowska, K. Orzechowski, M. Sierakowski, "Wedge-cell technique as a simple and effective method for chromatic dispersion determination of liquid crystals", Phot. Lett, Poland, 8(2), 51 (2016). CrossRef L. Deng, H.-K. Liu, "Nonlinear optical limiting of the azo dye methyl-red doped nematic liquid crystalline films", Opt. Eng. 42, 2936-2941 (2003). CrossRef J. Si, J. Qiu, J. Guo, M. Wang, K. Hirao, "Photoinduced birefringence of azodye-doped materials by a femtosecond laser", Appl. Opt., 42, 7170-7173 (2008). CrossRef